1990
DOI: 10.1111/j.1151-2916.1990.tb04269.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Dissolution of Sapphire in Calcia–Magnesia–Alumina–Silica Melts: Dissolution Kinetics

Abstract: The dissolution rate of sapphire into Ca0-Mg0-A1203-Si02 (CMAS) melts was investigated at 1450" and 1550°C. The effects of immersion time, specimen rotation rate, and magnesia concentration in the bulk melt on the sapphire dissolution rate and on the growth rate of magnesium aluminate spinel at the sapphire/melt interface were determined. The processes of direct and indirect sapphire dissolution into CMAS melts are discussed, with the support of kinetic and microprobe data.' A model of indirect sapphire dissol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 25 publications
2
64
0
1
Order By: Relevance
“…With this assumption, Sandhage et al 5) and Yu et al 7) concluded that mass transfer coefficient is suited to be expressed by the ) is expressed as follows:…”
Section: Rotation Speed In Alumina Dissolutionmentioning
confidence: 99%
See 3 more Smart Citations
“…With this assumption, Sandhage et al 5) and Yu et al 7) concluded that mass transfer coefficient is suited to be expressed by the ) is expressed as follows:…”
Section: Rotation Speed In Alumina Dissolutionmentioning
confidence: 99%
“…Considering the reported findings, [4][5][6][7] diffusion in the boundary layer was assumed as the rate-limiting step in the present study. With this assumption, Sandhage et al 5) and Yu et al 7) concluded that mass transfer coefficient is suited to be expressed by the ) is expressed as follows:…”
Section: Rotation Speed In Alumina Dissolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…THE rotating disk/cylinder (rod) method has been widely applied to study the dissolution of solids in liquids for decades, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] in particular for high-temperature systems such as dissolution of solid metals into liquid metals, and dissolution of ceramic solids into liquid oxides (slags). While valuable information have been gained by these studies, some misconceptions in using this method need to be addressed and analyzed.…”
Section: Introductionmentioning
confidence: 99%